2003
DOI: 10.1258/002367703766453038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repetitive sevoflurane anaesthesia on immune response, select biochemical parameters and organ histology in mice

Abstract: SummaryAnimal and technical models often require repeated anaesthetic administrations for surgical procedures. As there is evidence for immunomodulatory effects of anaesthesia, the effects of repeated exposure to sevo urane anaesthesia on the immune response in mice were studied. Sevo urane was administered in vivo under conditions that simulate those in clinical procedures. Adult male mice were anaesthetized with 3% sevo urane in oxygen for 40 min weekly for 3 weeks. Untreated animals served as controls. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 31 publications
1
31
0
3
Order By: Relevance
“…It has been shown that general anesthesia has immunmodulatory effects, including changes in natural killer cell activity and T-lymphocyte subpopulations, and augmented antibody secretion in mice (9,21). Specific humoral responses can become altered [i.e., increased as …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that general anesthesia has immunmodulatory effects, including changes in natural killer cell activity and T-lymphocyte subpopulations, and augmented antibody secretion in mice (9,21). Specific humoral responses can become altered [i.e., increased as …”
Section: Discussionmentioning
confidence: 99%
“…described by Elena et al (9)] after antigen administration and anesthesia; however, the latter cannot by itself influence the production of specific polyclonal antibodies. It has also been proposed that genes coding for HLA II may play a role in JORRP development.…”
mentioning
confidence: 99%
“…Here, we review the effects of some of the most common anaesthetic drugs (Table 1) on the immune system. Although some studies have showed effects of anaesthetic drugs on immune response even several days after their administration 9,13,14 , we will focus mainly on the effects within 24 hours after procedure, describing their effects on cells and cytokines of the innate and acquired immune systems.…”
Section: Mononuclear Phagocytesmentioning
confidence: 99%
“…Thus, part of the effect of anaesthetics on the immune system would be due to its action on the well-known immunomodulatory effect of glucocorticoids 3 . Diverse in vitro experiments with human immune cells 4 , ex vivo [5][6][7] , in vivo [8][9][10] or animal models have been used to study the effect of anaesthetic drugs on the immune system. .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that anesthetic agents given during any procedure may lead to immunosuppression (KELBEL and WEISS, 2001). Most clinical studies have been focused on the combined effects of surgery and anesthesia on the immune function (MORISAKI et al, 1998, DELOGU et al, 2000SCHNEEMILCH and BANK, 2001;HORI et al, 2003;COCELLI et al, 2012), with only a few studies dealing specifically with anesthetic agents (DAGAN et al, 1989;MOUDGIL and SINGAL, 1997;PUIG et al, 2002;ELENA et al, 2003;MÜLLER-EDENBORN et al, 2015).…”
mentioning
confidence: 99%